Analisis Hitung Jenis Leukosit sebagai Indikator Respons Imun Pascainjeksi Primer dan Sekunder Protein Rekombinan CIDR1α-PfEMP1 Dosis Bertingkat: Studi in Vivo pada Tikus Wistar - Asiya Audah (Fakultas Kedokteran, 2025)
Malaria remains a major public health concern, and vaccine development is an important strategy to combat it. The CIDR1α-PfEMP1 recombinant protein is a promising vaccine candidate. Previous study showed that the CIDR1α-PfEMP1 protein 150 μg + adjuvant induced a change in differential leukocyte count as part of the immune response. This study investigated the effects of various CIDR1αPfEMP1 protein doses on relative and absolute differential leukocyte counts. Twenty-eight Wistar rats were randomized and divided into four groups: control group (NaCl 0.9%), treatment groups of 75 μg + adjuvant, 150 μg + adjuvant, and 300 μg + adjuvant. Injections were conducted on days 0 (primary injection) and day 28 (secondary injection). Total leukocytes and differential leukocyte counts were measured on days 4 and 11 after the primary injection, and on days 4 and 14 after the secondary injection. Statistical analysis showed significant time related changes in eosinophil, neutrophil, and lymphocyte levels, reflecting the dynamics of the immune response after injection. The statistical analysis also showed no significant dose related differences in eosinophil, basophil, or lymphocyte counts, but significant differences in neutrophil and monocyte counts. There was a trend of increased in neutrophil at higher doses, and significant differences in relative counts between the control and 300 μg groups, and between the 75 μg and 300 μg groups in absolute counts. While monocytes showed a trend of decreased, with significant differences in relative counts between control and 150 μg group and in absolute counts between control and both the 150 μg and 300 μg groups. In conclusion, the CIDR1α-PfEMP1 recombinant protein at doses of 150 μg + adjuvant and 300 μg + adjuvant induced differential leukocyte count, especially neutrophil and monocyte, implying its potential as a vaccine candidate.
Reupload file repositori 09 Mei 2026_Maya FINALISASI oleh Arif 2026 Juni 15
Keywords: CIDR1α-PfEMP1; differential count; immune response; leukocyte; malaria vaccine